BOOK REVIEW: Rudolf Dinu, „L’avamposto sul Danubio della Triplice Alleanza. Diplomazia e politica di sigurezza nella Romania di re Carlo I (1878- 1914)”, collection „Dialogoi Politiké”, Aracne Publishing House, Ariccia (Italia), 2015, 212 pages - CÂRJA, Ion (Studia Universitatis Babeș-Bolyai Historia, 2017)
Rudolf Dinu is known as a historian both inside and outside Romania‟s borders particularly because of his contributions on topics touching on the history of international relations, diplomatic and political history and the history of Italian-Romanian relations from the second half of the 19th century – beginning of the 20th. He is a professor at the Faculty of History, Bucharest University, currently active in the field of cultural diplomacy: he was director of the Romanian Culture and Humanist Research from Venice and recently was appointed director at the Accademia di Romania in Roma. Among his most important scientific works we mention: 35 anni di relazioni italo-romene, 1879-1914. Documenti diplomatici italiani (Univers Enciclopedic Printing House, Bucharest, 2001, with Ion Bulei); Studi italo-romeni. Diplomazia e società, 1879-1914, Editura Militară Printing House, Bucharest, 2009); La Romania nella Grande Guerra. Documenti militari e diplomatici italiani 1914- 1918 (Editura Militară Printing House, Bucharest, 2014). The present book responds to a need of Romanian scientific research, research to which historians also contribute – externalisation, the real need to be better known outside the country and to publish in international languages. Rudolf Dinu has published in specialised magazines from Italy, respectively coordinated the publications of the Romanian Cultural Institute from Venice, Annuario and Quaderni, both serving the same goal which is to present to the Italian historiography topics of the Romanian history.